Newsies [videorecording (DVD)] - Menken, Alan; Redford, J. A. C. (Disney DVD., 2002)
July, 1899: When Joseph Pulitzer and William Randolph Hearst raise the distribution price one-tenth of a cent per paper, ten cents per hundred, the newsboys, poor enough already, are outraged. Inspired by the strike put on by the trolley workers, Jack "Cowboy" Kelly organizes a newsboys' strike. With David Jacobs as the brains of the new union, and Jack as the voice, the weak and oppressed found the strength to band together and challenge the powerful.